Analysis Reducing Slum Settlement by Road Improvement (A Case Study: Jawa Lama Village Village, Lhokseumawe, Aceh-Indonesia) - Herman Fithra; Sisca Olivia; Deassy Siska (Graduate Program of Syiah Kuala University, 2019)
a slum will cause many problems for many cities. The urbanization factor is one of the causes of slums due to the limited urban housing area. In general, there are seven slum indicators that can determine the quality of residential areas, one of which is physical infrastructure. Infrastructure conditions are interrelated with residential development. This study analyzes seven indicators of slums in Jawa Lama Village, Lhokseumawe, Aceh-Indonesia. In this study, the research team used data surveys with field tracking and field documentation from city roads. Documented data includes field photos and regional mapping that shows the location of the study. Data that has been collected can be used to determine urban facilities and infrastructure that are very influential for slums in the study area.